2022
DOI: 10.3390/sym14020182
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Boron: Boron-Containing Sugar Derivatives as Potential Agents for Boron Neutron Capture Therapy

Abstract: Boron neutron capture therapy (BNCT) is a binary type of radiotherapy for the treatment of cancer. Due to recent developments of neutron accelerators and their installation in some hospitals, BNCT is on the rise worldwide and is expected to have a significant impact on patient treatments. Therefore, there is an increasing need for improved boron delivery agents. Among the many small molecules and delivery systems developed, a significant amount of recent research focused on the synthesis of boron-containing su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…However, the boron delivery capacity was found to be significantly lower compared to our previous molecular libraries, , and especially, glucoconjugate 1 seemed to display a GLUT1 antagonist behavior rather than act as a promising delivery agent for BNCT. In addition to providing knowledge that may help explain earlier observations noted in the field, our results provide understanding on the boundaries within which this approach to BNCT can be further developed. The new insights on the substrate specificity of the GLUT1 transporter are important for the development of other therapeutic approaches centered on this molecular biology target.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…However, the boron delivery capacity was found to be significantly lower compared to our previous molecular libraries, , and especially, glucoconjugate 1 seemed to display a GLUT1 antagonist behavior rather than act as a promising delivery agent for BNCT. In addition to providing knowledge that may help explain earlier observations noted in the field, our results provide understanding on the boundaries within which this approach to BNCT can be further developed. The new insights on the substrate specificity of the GLUT1 transporter are important for the development of other therapeutic approaches centered on this molecular biology target.…”
Section: Discussionmentioning
confidence: 78%
“…Notable differences to our earlier work were observed. , In more detail, subtle structural modifications in the carborane and linker structures were found to significantly diminish the delivery capacity of these boron carriers. These results help identify the boundaries within which the GLUT1-targeting approach to BNCT can be further refined and aid in the interpretation of earlier observations noted in the field. …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Under such circumstances, growing numbers of reviews about BNCT has been published for the last few years, reflecting the increasing expectations. [ 1–12 ] In view of clinical applications, most of the reviews claim the need for novel 10 B carriers to meet the following requirements; 1) low intrinsic toxicity, 2) high boron accumulation in tumor ( 10 B/tumor tissue (wt/wt) ≥ 20 ppm), and 3) rapid clearance from blood and long persistence in tumor ( 10 B concentration ratio in tumor/blood (T/B ratio) ≥ 3). In light of low tumor specificity and retentivity of the two clinically used drugs, sodium borocaptate (BSH) and boronophenylalanine (BPA), [ 8 ] the 10 B carriers have been designed toward a nanometer size by conjugating boron agents with (bio)polymers and relatively large molecules, [ 13–15 ] encapsulating boron agents in micelles, [ 16,17 ] and incorporating boron atoms in nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…Boronated carbohydrate derivatives have received consideration in BNCT due to the preferential uptake of sugars by tumor cells, prompting us to design new BNCT theranostic agents based on monosaccharide scaffolds. Recently, new boronic acid derivatives have been synthesized introducing a boronic acid moiety into the sugar skeleton. Of interest is the fact that it has been reported that glucose membrane transporters tolerate modifications at the anomeric position of the sugar …”
Section: Introductionmentioning
confidence: 99%